If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -2) = 0 Reorder the terms: x(-2 + 2x) = 0 (-2 * x + 2x * x) = 0 (-2x + 2x2) = 0 Solving -2x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(-1 + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Simplifying x = 1Solution
x = {0, 1}
| 20x-2=18-4 | | 50+6x+27=3x+86 | | h(t) = -16t2 + 32t + 40 | | 6x-10x=4 | | (5w-8)(1-w)=0 | | 6x=5x+2(x-1)-x+b | | (x-4)-(3-2x)=(3x+4)-(6+x) | | ln(5x-12)=9 | | Y-a=26 | | n^2-2n-3=6 | | x^2+6x=130 | | (3+2i)(3+2i)=0 | | 10m=k^2 | | 4g+3=23 | | X^2+5-104=0 | | 3n=30-3 | | x=48 | | 6x^3-13x^2-8x= | | 14=-16t^2+24t+6 | | g(b+6)=7x-2 | | 2+m=3 | | -2h+5=5h-44 | | N^2+10=-5n | | 5n=26+4 | | 6x=11x^2 | | -5h+6=41 | | x-10+x+30=120 | | 3x+=5x-1 | | 2(7x-55)=7x-20-2x | | x-10=120 | | 4x+2(x+5)-3x=3x+20 | | 0=x^2-8x-4 |